Trace Elements in Sediment and Urban Water Samples: an Assessment of Metal Pollution - De Almeida, Jéssika Aparecida Santos; Quinaia, Sueli Pércio; Nunes, Chalder Nogueira; Jansen, Aline Bortolanza; De Oliveira, Izabelly Izabelly Karol Poncio (Anuário do Instituto de Geociências, 2023)
In this study, trace elements (Cd, Cr, Cu, Pb and Zn) concentrations were determined by flame atomic absorption spectrometry (FAAS) in environmental compartments (water and superficial sediments) near places of vehicle use and maintenance, aiming to investigate if in these places the trace elements had high concentrations. The content of trace elements found on the samples was compared to the maximum values recommended by resolutions of CONAMA (Conselho Nacional do Meio Ambiente) n. 357 from 2005 for water and n. 454 from 2012 for sediments. Points 11 and 13 were the most critical, with concentrations higher than the recommended for the elements Cu and Pb, either for water or sediment samples. Geoaccumulation index (Igeo) for Cd and Cr in the sediment samples indicated high to extreme contamination in points 5 and 13, while the other elements indicated moderated contamination.